BUSINESS ARCHITECTURE OF THE BANKING SECTOR: CONTENT AND DETERMINING PARAMETERS OF FORMATION - TKACHENKO, Oleksandr (Scientific journal «World of Finance», 2024)
Introduction. The banking sector is one of the most dynamic spheres of economic life. That is why the problem of forming an effective business architecture of the banking sector, which would ensure its financial stability and contribute to the economic development of the national economy, is important.The purpose of the article is to substantiate the content of business architecture, based on the specifics of the banking sector, and outline the fundamental factors of its formation.Results. The main markers determining the need to ensure the continuity of the banking sector are outlined. The components of the continuity management system of the banking sector are defined. The substantive difference between the concepts of "bank business model", "bank strategy" and "business architecture of the banking sector" is formulated according to the criterion approach. The scientific position on the classification of business models of banks is summarized. The author's vision of the two-level structuring of the bank's business model is presented.Conclusions. It is proven that the main requirements for the modern banking sector as a highly adaptive system are its openness and self-organization, purposefulness, emergency, integrity, reliability, flexibility and sustainability. The prerequisite for achieving the above is the optimal business architecture of the banking sector, which, in turn, is derived from the interaction of the business models of banks presented on the market. It is substantiated that in the conditions of the modern digital transformation of the economic space, it is important to comprehensively and multi-facetedly identify the business models of banks, which would take into account modern trends.